(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2025)
This paper investigates the complex relationship between digital disinformation, hate speech, and human rights in Indonesia. The rapid growth of social media platforms in the country has brought both opportunities and challenges for public discourse, with the proliferation of disinformation and hate speech posing significant risks to social harmony and individual rights. The study critically assesses Indonesia’s legal frameworks, including the Information and Electronic Transactions Law (ITE Law) and its provisions on online defamation and hate speech. Through a detailed examination of recent cases, the paper explores the tension between protecting freedom of expression and curbing harmful content. Interviews with legal experts, social media users, and human rights advocates highlight the difficulties in balancing these interests, especially given the country’s diverse religious and ethnic landscape. The findings indicate that while there is growing recognition of the harm caused by disinformation and hate speech, existing laws are often applied in ways that disproportionately affect marginalized groups and stifle free expression. The paper proposes policy recommendations for refining hate speech regulations, including clearer legal definitions, improved enforcement mechanisms, and stronger protection for freedom of speech online.